Crecimiento económico y distribución del ingreso en el Perú - Jannina, Quilca (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
Since the economic recovery in the 1990s, the Peruvian economy has presented a favorable situation in terms of economic growth; however, income inequality in the country remains almost constant. In this context, the purpose of this research is to study the existence of a statistically significant relationship between economic growth and income distribution in Peru in the period 1990-2014, being important for its contribution to providing a better vision for the development of the economic policy in terms of reducing inequality; and preparation of short- or long-term corrective measures. For the development of the research, statistical data were collected, and an econometric model of Ordinary Least Squares was built, taking as a dependent variable the natural logarithm of GDP per capita to explain growth and as an independent variable to measure the level of inequality determined by the Gini Coefficient, as well as control variables used to give consistency to the model. The results suggest the existence of a quadratic relationship between economic growth and income inequality; they also explain that the Peruvian economy is in the first stage of the inverted U relationship between growth and inequality, raised in the economic literature.